TAKTIK PEMASARAN RELASIONAL PADA 21CINEPLEX - , Ria Oktriana Nurwijayanti, S.Sos.; , Dr. Iin Mayasari, M.M., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dynamic changes in the world of business have a big influence in the marketing strategy, characterized by the emergence of a critical behavior of customers in consumer products. This development requires an appropriate marketing strategy, one of which is relationship marketing. Some relational marketing tactics are real appreciation, preferential treatment and communication between the personas. The purpose of this study was to determine the customer's perception of the application of relationship marketing tactics undertaken by cinema 21Cineplex, therefore this research is descriptive. Primary method of data collection was conducted by survey method by giving questionnaires to a sample selected by non probability sampling technique. Types of non-probability purposive sampling are used, so the selected respondents totaled to 250 regular customers and have certain characteristics. Analytical techniques used in this study are to use average/mean to determine the individual's perception of relationship marketing tactics by the company. The results show that overall customer perception of relationship marketing tactics on the application of the company has a good value. This means the application of relationship marketing tactics are perceived both by customers and the assessment results are above average.